The Effect of Couple-Stresses on Stress Concentration Around a Rigid Circular Inclusion in a Half-Plane Under Tension - Itou, S. (Engineering Transactions, 1977)
The two-dimensional linearised theory of couple-stress elasticity has been applied to investigate the stress distribution in a half-plane having a perfectly rigid circular inclusion. Simple tension acts in parallel to the plane boundary. The solution is illustrated by some numerical results.